Achieving Person-Centred Health Systems Evidence, Strategies and Challenges - Nolte, Ellen; Merkur, Sherry; Anell, Anders (Social Sciences, 2020)
Individuals, their families and communities should have a greater role in the health system, but how this can be achieved in practice remains challenging. This volume explores how a person-centred approach can meet the various challenges health systems are facing today and guides policymakers towards more informed policies and practices.